LOAN MORATORIUM 2020- ITS IMPACT ON INDIAN BANKS - Mehta, Meera; Kaul, Rishab (Australian Finance & Banking Review, 2020)
Moratoriums area period of temporary suspension of an activity or law till a decision to lift the suspension is made, as in the case of the issues that led to the moratorium are resolved. Moratoriums may be imposed by regulators, by a business, or by the government. A moratorium is often ordered in response to situations of crisis. Moratoriums are not new to the Indian banking sector and have been granted and imposed in multiple instances in the last 20 years. Since 1999 moratoriums have been imposed on 9 banks for various reasons. Recently, a six-month moratorium was offered by the Reserve Bank of India (RBI) between March 1, 2020, and August 31, 2020, on all loan equated monthly instalments, to help lessen the troubles faced by the borrowers due to the COVID-19 pandemic. This paper aims to study the recently granted moratorium by the RBI to assess and predict its impact on the banking sector. The study will also reflect on similar instances of moratoriums that have been granted in the United States, Greece, and Thailand in the last 20 years.